Nos braços da resistência: o espaço da educação popular nos cursos de licenciatura da Universidade Federal da Fronteira Sul Campus Erechim/RS - Andrade, Daiane Bornelli de (2020)
This study has as its research theme popular education in undergraduate courses at the Federal University of Fronteira Sul - Campus Erechim. The objective on which this research is based is to identify whether the undergraduate courses at UFFS Campus Erechim / RS include the “popular emancipatory” dimension defended in its official documents, seeking to understand, in practice, how this dimension is constituted. The methodology configures a quantitative-qualitative study of exploratory and descriptive type that has as instruments of data collection the questionnaire to survey the profile of the undergraduate academic, documentary analysis of the Institutional Development Plan of the university, as well as the Pedagogical Projects of the Licentiate Courses. It also has a semi-structured interview with representatives of entities that were part of the UFFS installation process in the city of Erechim, graduates, graduates, coordinators of the institution's six degrees. The organization and analysis of data occurs from three analytical categories, called dimensions. The first category corresponds to the “Mobilizing dimension of the subjects: choice, permanence and continuity”. The second category of analysis is related to the “Political dimension: mishaps and advances in popular education at UFFS Campus Erechim / RS”. The third category examines the curricula of undergraduate courses and is called “Pedagogical dimension: popular education in undergraduate curricula”. The collected data were sewn with analyzes in the fields of popular education: BRANDÃO (2002; 2008; 2014), CARRILLO (2007); FREIRE (1979; 1980; 1987; 2000a, 2002), among others. BOURDIEU; PASSERON (2010), BOURDIEU (1998), MÉSZARÓS (2008) MARTUCELLI (2007), among others, served as a source of analysis for questions of a sociological nature. Regarding the curriculum, the investigation is based on APPLE (1994), SACRISTÁN (2000), SILVA (2017), among others. Based on this research, it became possible to assess the scope of popular education in the undergraduate courses at UFFS Campus Erechim / RS, both with regard to the official curriculum, as well as in the spaces and experience within the university environment. It was found, from this study, that popular education is present in the institution in the theory proposed in the official documents, in its spaces, in extracurricular activities, in the experiences and debates promoted by the transversality of the themes discussed in the classroom . However, the theme is not considered significantly in the curricula of most courses at the institution. Therefore, the researcher's commitment to the requirement of the Professional Master's Degree in Education, of socializing research data for the academic and general community, is reiterated, since the results obtained will be of great value for possible contributions to the undergraduate courses at UFFS Campus Erechim / RS.